2016
DOI: 10.1007/s12192-016-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermotolerance and molecular chaperone function of an SGT1-like protein from the psychrophilic yeast, Glaciozyma antarctica

Abstract: The ability of eukaryotes to adapt to an extreme range of temperatures is critically important for survival. Although adaptation to extreme high temperatures is well understood, reflecting the action of molecular chaperones, it is unclear whether these molecules play a role in survival at extremely low temperatures. The recent genome sequencing of the yeast Glaciozyma antarctica, isolated from Antarctic sea ice near Casey Station, provides an opportunity to investigate the role of molecular chaperones in adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Functions of the SGT1 protein and the TPR domain in protists are virtually unknown. Over-expression of SGT1 in Glaciozyma antarctica protected this yeast from high and low temperature stresses [ 49 ]. Prior to the current study, only one protein of the SGT1 network was annotated from a kinetoplastid genome: T .…”
Section: Resultsmentioning
confidence: 99%
“…Functions of the SGT1 protein and the TPR domain in protists are virtually unknown. Over-expression of SGT1 in Glaciozyma antarctica protected this yeast from high and low temperature stresses [ 49 ]. Prior to the current study, only one protein of the SGT1 network was annotated from a kinetoplastid genome: T .…”
Section: Resultsmentioning
confidence: 99%
“…Cold-adapted enzymes generally exhibit an increased glycine content and reduced arginine, proline, and acidic amino acid contents [64]. Structural studies on cold adaptation have also revealed that a modest substitution with alanine increased the structural ability of a protein to function in the cold while maintaining its rigidity and stability [65]. The analysis of the protein structure at the atomic level showed that several substitutions could hinder the strong force and contribute to protein rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…The methods that we have developed from available and proven tools are expected to be easily deployable to other genomes as and when they become available with minimal modifications. Recently, a psychrophilic yeast genome had been reported [ 33 ] that has other functional data also available such as gene expression during cold stress [ 34 , 35 ] and the characterization of proteins involved in cold adaptation [ 36 38 ]. The mining of such genomes for sORFs that can then be integrated to the functional data may be a cost-effective means of identifying sORFs that are involved in psychrophily or other relevant extremophilic adaptations.…”
Section: Discussionmentioning
confidence: 99%